2007
DOI: 10.1111/j.1365-2427.2007.01698.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth, production and bioenergetics of brown trout in upland streams with contrasting riparian vegetation

Abstract: 1. A series of laboratory-based equations on trout growth and bioenergetics developed by J.M. Elliott were applied to data collected for brown trout (Salmo trutta L.) under field conditions in Co. Mayo, Western Ireland. Fish were collected by electrofishing eight upland streams with contrasting riparian vegetation; grassland, open canopy and closed canopy deciduous. 2. Stream temperatures, one of the main influencing factors on fish growth and energetics, did not differ significantly between riparian types. 3.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 82 publications
0
9
0
Order By: Relevance
“…Riparian cover is hypothesized to influence fish or amphibian occurrence and abundance in Northern California (Welsh et al 2005) and Japan (Inoue andNunokawa 2005, Nakamura andYamada 2005). However, Dineen et al (2007) found that riparian cover did not influence stream water temperature in for-ested Northern Ireland, and speculated that increased terrestrial subsidies in forested streams were important in maintaining growth of trout. Saunders and Fausch (2007) showed that intensive grazing by livestock reduced riparian vegetation and led to decreased input of terrestrial invertebrates, thereby reducing foraging opportunities for trout in mountain grassland streams.…”
Section: How Ecological Responses Of Animals Change Across Biome Gradmentioning
confidence: 99%
“…Riparian cover is hypothesized to influence fish or amphibian occurrence and abundance in Northern California (Welsh et al 2005) and Japan (Inoue andNunokawa 2005, Nakamura andYamada 2005). However, Dineen et al (2007) found that riparian cover did not influence stream water temperature in for-ested Northern Ireland, and speculated that increased terrestrial subsidies in forested streams were important in maintaining growth of trout. Saunders and Fausch (2007) showed that intensive grazing by livestock reduced riparian vegetation and led to decreased input of terrestrial invertebrates, thereby reducing foraging opportunities for trout in mountain grassland streams.…”
Section: How Ecological Responses Of Animals Change Across Biome Gradmentioning
confidence: 99%
“…In salmonids, spatio-temporal variations in population abundance and production are closely related to differences and changes in physical habitat conditions Lobó n-Cerviá & Rincó n 2004). Further, together with other essential biotic and abiotic factors, habitat quality and quantity influence many population traits such as survival (Harvey et al 2005;Lobón-Cerviá 2007), growth (Harvey et al 2005;Dineen et al 2007) or migration rates (Belanger & Rodriguez 2002), as well as pervasive biological processes like self-thinning (Lobó n-Cerviá 2008), that affect population dynamics. Habitat selection is perceived as an adaptive complex behaviour faced by organisms at the individual level, but shapes many key biological processes whose patterns emerge at higher organisation levels (Grimm & Railsback 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Ten studies were identified following full text assessment, and from which data could be retrieved (see Additional file 4) [34][35][36][37][38][39][40][41][42][43]. These studies were in: New Zealand (3), UK (2), USA (2), Ireland (1), Spain (1) and Denmark (1).…”
Section: Groupmentioning
confidence: 99%